IMPLEMENTASI NILAI BUDAYA DALAM TRADISI KIRAB BUDAYA KANJENG IBU MAS SEMANGKIN SEBAGAI UPAYA PELESTARIAN KEARIFAN LOKAL JEPARA - Aqilah Latujtaba; Luthfa Nugraheni (Universitas Muria Kudus, 2025)
The aim of this research is to determine the cultural values ​​in the Kanjeng Ibu Mas Semangkin Mayong Jepara cultural haul and carnival traditions.This study examines the implementation of the haul tradition and cultural procession of Kanjeng Ibu Mas Semangkin in Mayong Lor Village, Jepara Regency, as a manifestation of local culture. Held routinely every 15th of Muharram, this tradition includes various activities that reflect religious, symbolic, and social values, such as Khatmil Quran, istighasah, cultural procession and buka luwur, as well as public religious studies. Clifford Geertz's interpretive ethnography is used to understand how cultural meaning is constructed and maintained through community social interactions. This study found that although this tradition is developing dynamically, it is hampered by not being officially registered with the Jepara Regency Tourism and Culture Office. This has resulted in a lack of recognition and institutional support necessary for its continued preservation. Therefore, this study recommends that the community collaborate with the local government to register this tradition with the office to strengthen its institutional sustainability. The aim of these cultural values ​​is (1) to appreciate roles, (2) to ask for mercy, (3) to strengthen togetherness, and (4) to maintain the values ​​of faith.